PERAN AUDIT INTERNAL DALAM MENINGKATKAN AKUNTABILITAS DAN TRANSPARANSI LAPORAN KEUANGAN RUMAH SAKIT - YOLANDA SAFITRI NELAZ; DINNA NURHASANAH; NENI AFRIYANI; BELLA PUTRIE NINDYAWAN (JURNAL AKUNTANSI DAN KEUANGAN, 2025)
This research analyzes the role of internal audit in improving the accountability and transparency of hospital financial statements. Hospitals, as health service institutions, are required to manage finances from various sources according to standards and regulations. Using qualitative descriptive methods and a case-study approach, data was collected from interviews, questionnaires, and document analysis in several hospitals with active internal audit units in Pekanbaru. Results indicate that effective internal audit implementation enhances planning, scope, standardization, and communication of findings to management, significantly improving the accuracy and compliance of financial statements. Despite encountering challenges such as limited resources and work culture, internal audit remains central for continuous improvement in financial governance. These findings suggest that strengthening internal audit capacity and support systems is vital for trustworthy and transparent reporting in hospitals.